Responsabilidad social empresarial en empresas chihuahuenses que obtuvieron el distintivo ESR 2013. (2016)
Corporate social responsibility (RSE- for its spanish acronym) has become a worldwide trend. Our objective was to evaluate the implementation of the practice of social responsibility in Chihuahuenses companies that obtained the Socially Responsible Company (ESR- for its spanish acronym) award. The nature of the research was mixed, applied and not experimental. The population of interest were Chihuahuenses companies with the ESR 2013 award. Most of them specified that the main advantage of implementing ESR practices is the preservation of the environment, increased performance of human capital, attracting investors and increased sales. Furthermore, it was noted that an added value to services is granted providing an opportunity for companies to be more competitive and profitable.